Synthesis & identification some heterocyclic compounds derivatives of Biotin - Retha, Nabeel A.A.AL.; Farhan, Ali M. (Al-Qadisiyah Journal of Pure Science, 2017)
The studies involves synehesis some new derivatives for the biotin by many schemes . The first scheme involve treatment the biotin with methanol in present sulfuric acid concentration to obtained the derivative [H1], the derivative [H1] has been treated with hydrazine hydrate to obtained the derivative [H2] , for there treatment the derivative [H2] with acetyl acetone to obtained the derivative [H3] , and also treated the derivative [181] with carbon disulphide in present potassium hydroxide obtained the derivative [H4] . Either the second scheme involves treat ment the biotin with thiosemacarbazide in present Phosphorous oxy chloride to obtained the derivative [H5] which treated with Phthalic anhydride and Malic anhydride to obtained the derivatives [H6] & [H7] respectively, and also treatment the derivative [H5] with P-N,N-Dimethyl amino benzaldehyde to obtained on Schiff base the derivative [H8] which consider intermediate to preparation the derivative [H9] after with treatment Thio acetic acid .